A randomized controlled trial of Tickoff® (Metarhizium anisopliae ICIPE 7) for control of tick infestations and transmission of tick-borne infections in extensively grazed zebu cattle in coastal Kenya - Joseph Wang’ang’a Oundo; Shewit Kalayou; Gerrit Gort; Gebbiena M. Bron; Constantianus J.M. Koenraadt; Quirine ten Bosch; Daniel Masiga (Parasite Epidemiology and Control, 2024)
The entomopathogenic fungus Metarhizium anisopliae isolate ICIPE 7 is being developed as an eco-friendly alternative to chemical acaricides in managing natural tick infestation on livestock. Its impact on tick infestation and tick-borne infections in cattle under natural conditions are yet unclear. We conducted a randomized controlled field trial to assess the safety and effects of Tickoff® (a formulation of M. anisopliae isolate ICIPE 7) and the chemical acaricide Triatix® on tick infestation and incidence of Anaplasma marginale and Theileria parva in extensively grazed zebu cattle in coastal Kenya. A total of 217 eligible herds comprising 1459 intent-to-treat zebu cattle were enrolled from 12 villages. The herds were randomly assigned in a 1:1:1 ratio to Tickoff®, Triatix®, or Tickoff® excipients. Tick counts, treatment administrations, and adverse events were registered every two weeks for seven months. The mortality of ticks collected from treated cattle was monitored in vitro. Infections with A. marginale and T. parva were monitored every two months. No adverse events were reported in either treatment group. Tickoff® did not significantly affect tick infestation (p = 0.869) or infection incidence (p > 0.05) compared to excipients. Triatix® significantly reduced tick infestation (p < 0.001) and incidence of T. parva (p = 0.042), but not A. marginale (p = 0.509) compared to the reference Tickoff®. In ticks that were removed from cattle, Tickoff® demonstrated significant pathogenicity in vitro relative to excipients (hazard ratio: 8.50, 95 % CI: 4.67–15.47). Fungus growth and sporulation were also observed on tick cadavers from Tickoff®, but not from excipients. While Tickoff® did not impact tick counts, its delayed, but significant effect on tick mortality may hinder onward pathogen transmission and give rise to indirect (i.e., to untreated animals) epidemiological effects, that were not picked up with this study design. Additionally, adverse environmental conditions resulted in low tick abundance and pathogen circulation towards the end of the study period, reducing the power of the study. This work re-emphasizes the challenges of randomized controlled field trials and the complexity of assessing the impact of vector control products on both direct and indirect impacts on pathogen transmission.